THE ROLES OF LEARNING ACTIVITIES ON EMPLOYEES’ PERFORMANCE IN MANUFACTURING FIRMS AT PENANG, MALAYSIA - AMIN, BOKHORI MD (International Journal of Multidisciplinary Research and Studies, 2019)
This study evaluated the relationship between workplaces learning activities, outdoor learning activities, and continuous learning activities on employees' performance in manufacturing firms in Penang, Malaysia. A sample size of 222 respondents was taken from 28 electrical manufacturing firms with a 6322 population and 361 samples to examine the relationship. A questionnaire was designed for data collection to measure learning activities on employees' performance in manufacturing firms. A stratified sampling method was used, and the data was analyzed using SmartPls 3.7.8. The study showed that workplaces learning activities and continuous learning activities have a significant relationship with employees' performance in manufacturing firms. The result also showed that outdoor learning activities are not-significant on employees’ performance in manufacturing firms. However, the limitation of this study only covers electrical manufacturing firms. Suggested for future study focus on electronic, plastic, and fabricated manufacturing firms to be more effective in improving manufacturing firms' learning and development practices.